Eco-efficiency analysis of water distribution system flushing into a containment Pond. (1st November 2022) - Sheefa, Darud E.; Handler, Robert M.; Barkdoll, Brian D.
Abstract: For a salt or other conservative contaminant contamination event in a water distribution system, opening fire hydrants to flush the system is currently an accepted decontamination method. However, all the contaminated flushed water is discharged to the local surroundings of the fire hydrants and imposes an environmental impact. Another system decontamination alternative can be using a containment pond to catch the contaminated water. To reduce environmental impacts of flushing salt from a water distribution system a comparative life cycle assessment study has been performed for both conventional flushing and for flushing contaminated water into a containment pond. This was performed using SimaPro software for both of these decontamination options and the impacts have been assessed using the IMPACT 2002+ methodology. The results show that environmental impacts can be reduced by 25% for rural areas, 69% for urban roads, 61% for urban lawns, and 64% for mixed land use. In addition, a sensitivity analysis reveals the two most sensitive variables resulting in the finding that a 10% change in the time needed for system decontamination led to a 10% change in environmental impact and a 10% change in the area of land exposed to contaminated water discharge led to an 8% change in environmental impact. Highlights: Flushing salt into a containment pond(s) increases environmental impact. Salt discharge to a pond avoids damage to concrete from regular flushing. The use of a containment pond in urban areas reduces environmental impact by more than 50% over conventional flushing. Flushing to agricultural lands or lawns can impose less impact than a combined environment. Flushing time and exposed land area are the most sensitive variables have the most difference.